Numerical Solution of Fractional Model of HIV-1 Infection in Framework of Different Fractional Derivatives - Sara Salem Alzaid; Badr Saad T. Alkahtani; Shivani Sharma; Ravi Shanker Dubey (Journal of Function Spaces)
In this paper, we have extended the model of HIV-1 infection to the fractional mathematical model using Caputo-Fabrizio and Atangana-Baleanu fractional derivative operators. A detailed proof for the existence and the uniqueness of the solution of fractional mathematical model of HIV-1 infection in Atangana-Baleanu sense is presented. Numerical approach is used to find and study the behavior of the solution of the stated model using different derivative operators, and the graphical comparison between the solutions obtained for the Caputo-Fabrizio and the Atangana-Baleanu operator is presented to see which fractional derivative operator is more efficient.